PERDEBATAN IDEOLOGI PENDIDIKAN - Karti Soeharto (Jurnal Cakrawala Pendidikan, 2010)
Abstract: Debates on Educational Ideologies. The study of educational ideologiesderives from perspective debates between the formal system perspective and theprocess perspective. The formal educational ideology has applied the generalphilosophical system since 1950, whereas the process or problematic perspectiveusing the semantic, rational, and empirical methods has refused the former since1960. Today, this dispute is still going on. Based on ONeills taxonomy, theeducational ideology in Indonesia can be classified as a conservative socialrevisionist ideology or liberal compromise ideology.Keywords: educational ideology, conservative social revisionist ideology, liberalcompromise ideology